Time-series analysis of meteorological factors and emergency department visits due to dog/cat bites in Jinshan area, China - Pang, Pei; Zhou, Xiaoyong; Hu, Yabin; Zhang, Yin; He, Baoshi; Xu, Guoxiong (PeerJ, 2024)
Background Meteorological factors play an important role in human health. Clarifying the occurrence of dog and cat bites (DCBs) under different meteorological conditions can provide key insights into the prevention of DCBs. Therefore, the objective of the study was to explore the relationship between meteorological factors and DCBs and to provide caution to avoid the incidents that may occur by DCBs. Methods In this study, data on meteorological factors and cases of DCBs were retrospectively collected at the Shanghai Climate Center and Jinshan Hospital of Fudan University, respectively, in 2016–2020. The distributed lag non-linear and time series model (DLNM) were used to examine the effect of meteorological elements on daily hospital visits due to DCBs. Results A total of 26,857 DCBs were collected ranging from 1 to 39 cases per day. The relationship between ambient temperature and DCBs was J-shaped. DCBs were positively correlated with daily mean temperature (rs = 0.588, P < 0.01). The relative risk (RR) of DCBs was associated with high temperature (RR = 1.450; 95% CI [1.220–1.722]). Female was more susceptible to high temperature than male. High temperature increased the risk of DCBs. Conclusions The extremely high temperature increased the risk of injuries caused by DCBs, particularly for females. These data may help to develop public health strategies for potentially avoiding the occurrence of DCBs.
Keywords: Distributed lag non-linear model (DLNM); Meteorological factors; Emergency department visits; Dog and cat bites (DCBs); Relative risk